2022
DOI: 10.3390/horticulturae8121141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blue Light on Plant Growth, Flowering and Accumulation of Medicinal Flavones in Scutellaria baicalensis and S. lateriflora

Abstract: Scutellaria baicalensis Georgi (Baikal skullcap) and S. lateriflora (American skullcap) are two ethnobotanical medicinal plants used to treat gastrointestinal, respiratory, and inflammatory disorders, in addition to demonstrated anti-cancer properties. The predominant bioactive compounds produced in these species are unique 4′-deoxyflavones, in roots of S. baicalensis and leaves of S. lateriflora, making these two species suitable to study the effects of light quality on flavone accumulation in aerial and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Scutellarein, a common ingredient identified in many herbal medicines, such as Scutellaria baicalensis (79) and Perilla frutescens (29,80), was reported to exert anti-microbial, anti-viral, anti-tumor, hepatoprotective, anti-neurodegenerative, and anti-oxidant effect (81). As the previous studies showed, scutellarein from different sources, including Indian medicinal plants, Perilla frutescens, Salvia plebeia, and Salvia officinalis L., had a potent inhibitory effect on XDH in vitro (29,73,77,82) and played a significant role in reducing the serum uric acid in vivo (77).…”
Section: Discussionmentioning
confidence: 99%
“…Scutellarein, a common ingredient identified in many herbal medicines, such as Scutellaria baicalensis (79) and Perilla frutescens (29,80), was reported to exert anti-microbial, anti-viral, anti-tumor, hepatoprotective, anti-neurodegenerative, and anti-oxidant effect (81). As the previous studies showed, scutellarein from different sources, including Indian medicinal plants, Perilla frutescens, Salvia plebeia, and Salvia officinalis L., had a potent inhibitory effect on XDH in vitro (29,73,77,82) and played a significant role in reducing the serum uric acid in vivo (77).…”
Section: Discussionmentioning
confidence: 99%
“…Scutellaria lateriflora (American skullcap) and Scutellaria baicalensis Georgi (Baikal skullcap) are two ethnobotanical medicinal plants used to treat gastrointestinal, respiratory, and inflammatory disorders, in addition to demonstrated anti-cancer properties [78]. The predominant bioactive compounds produced in these genotypes are unique 4-deoxyflavones, in the roots of S. baicalensis and leaves of S. lateriflora [78]. For these skullcap plants grown indoors under sole-source lighting with a broad spectrum, higher BL proportions benefit flowering and morphology, but its effects on other metrics vary with plant genotype.…”
Section: Specialty Cropsmentioning
confidence: 99%
“…For these skullcap plants grown indoors under sole-source lighting with a broad spectrum, higher BL proportions benefit flowering and morphology, but its effects on other metrics vary with plant genotype. For example, sole-source lighting with higher-BL broad-spectrum LED (84% B) resulted in earlier flowering, caused more compact plants, and increased flavone accumulation in leaves for S. lateriflora but decreased it in roots for S. baicalensis Georgi, compared with lower-BL broad-spectrum LED (18% B) [78].…”
Section: Specialty Cropsmentioning
confidence: 99%